Recuperação de ouro de elevada pureza a partir de pinos conectores de CPU de computadores obsoletos via processamento hidrometalúrgico - Tássio Baêta Zille Gontijo (2019)
New gold deposits are scarce, with the metal grade ore decreasing and its mineralogy getting more complex. In this scenario, electrical and electronic wastes represent an important secondary source due to the large amounts generated and appreciable Au contents in some components. This work describes the recovery of high purity gold from connector pins of computer CPU, which were manually separated. The experimental approach consisted in leaching of uncut pins or cut pins aiming at dissolve the metals present in the pins and maintain gold in the metallic form. The samples were characterized by chemical composition and structure using EDX, SEM-EDS and ICP-OES. The analyses indicated that the substrate of the pins is constituted by Cu-Fe, Ni-Fe or Fe-Ni-Co alloys, with thin external Au coating (<10 μm) on intermediate Ni coating (Cu-based substrates) or Ni-Co coating (Fe-Ni-or Fe-Ni-Co-based substrates). The following chemical composition was determined: Cu 43.1% wt., Fe 26.1% wt., Ni 20.0% wt., Co 4.6% wt. and 1.4% wt.. The samples of uncut or cut pins were initially leached in the system H2SO4-H2O2. Two leaching stages of uncut pins (conditions: 1.0 mol/L H2SO4, 6.7% v/v H2O2, 35 g/L S/L ratio, 15 min, 400 min-1-1ststage and 800 min-12ndstage) resulted in global Cu leaching around 65-75% and production of sulfate liquor containing 5-6 g/L of Cu. Two leaching stages of cut pins under similar conditions resulted in global Cu leaching around 78-92% and production of liquor containing 7-8 g/L of Cu. The leaching residues were rinsed in the HCl-H2O2 system in order to further concentrate the gold in the solid phase. After two leaching stages (conditions: 2.0mol/L HCl, 1.0% v/v H2O2, 12 g/LS/L ratio, 45 min, 200 min-1), the residues were finally rinsed with HCl solution (4 mol/L) and characterized. The overall Au recovery was (98 ± 2)% from uncutpins and (99 ± 1)% fromcut. The final product obtained contained approximately (99.2 ± 0.8)% and (99.4 ± 0.5)% Au from the treatment of uncut and cut pins, respectively.